SELF-REGULATED LEARNING IMPLEMENTED BY THE STUDENTS OF VOCATIONAL HIGH SCHOOL - P.I.M., Sari (International Journal of Language and Literature, 2019)
This study aimed at identifying whether the students of vocational high school in Buleleng sub-district have implemented self-regulated learning or not. Besides, analyzing the mostly implemented aspects of self-regulated learning was the other purpose of this study. The subject of this study were 405 students of vocational high schools in Buleleng sub-district. There were SMKN 2 Singaraja, SMKN 3 Singaraja, and SMK Triatmajaya Singaraja. Descriptive qualitative was used as the design of this study. Some instruments were used, such as questionnaire, observation checklist, and interview guide. The result of this study showed that self-regulated learning has been implemented by 75% vocational high schools students. Besides, there are three aspects which mostly implemented by students of vocational high school, they are self-control, self-judgment, and self-reaction based on Zimmerman cyclical phase theory